A Sustainable Model for Heritage Property: an Integrative Conceptual Framework - Afiqah Md. Azmi, Fatin; Ismail, Suriatini; Ab. Rahman, Rosdi; Tahir Sabit, Mohammad; Mohammad, Junainah (International Journal of Engineering and Technology, 2018)
Malaysia is one of the developing countries but the management and investment by the local authority and investors in the heritage property remain limited which are apparent in the literature. Studying an integrative literature review is the most appropriate way to address the problem of heritage property. It is indicated that the local planning authorities do not have the financial capacity for providing incentives because the conservation and preservation works are costly. If the heritage property is neglected, deteriorated, and dilapidated, the value of archaic services may be affected. The objective of this paper is to review the heritage management system in Malacca and Penang, considering the institutional, legal, and resources frameworks and concerning on the heritage conservation, investment, and valuation. In this study, some variables have been obtained by database that can be used to evaluate the existing frameworks. Finally, all variables are summarized in a new sustainable model by identifying the gaps in the local literature. It is hoped that the present review would be considered as a kind of strategy for the future research and has made substantive contributions to the knowledge as well as inventing new thinking in the field of heritage property.Â Â